2023
DOI: 10.1007/s41669-022-00383-x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Nivolumab Versus Docetaxel for the Treatment of Advanced Squamous and Non-squamous Non-small Cell Lung Cancer After Prior Chemotherapy in China

Abstract: Objective To evaluate the economic value of nivolumab versus docetaxel for advanced non-small cell lung cancer (aNSCLC) treatment after platinum-based chemotherapy in adults without epidermal growth factor receptor/anaplastic lymphoma kinase aberrations in China. Methods Partitioned survival models evaluated lifetime costs and benefits of nivolumab versus docetaxel by squamous and non-squamous histologies from a Chinese healthcare payer perspective. Progression-free dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Two of the studies based their judgments on ICERs. The Hu 2023 [ 49 ] study results showed an increase of RMB ¥207,388 (US $31,537) per QALY for nivolumab versus docetaxel ICER in squamous aNSCLC. Rothwell 2021 showed ICERs of £33,134 for nivolumab in patients with LSCC compared to docetaxel.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies based their judgments on ICERs. The Hu 2023 [ 49 ] study results showed an increase of RMB ¥207,388 (US $31,537) per QALY for nivolumab versus docetaxel ICER in squamous aNSCLC. Rothwell 2021 showed ICERs of £33,134 for nivolumab in patients with LSCC compared to docetaxel.…”
Section: Resultsmentioning
confidence: 99%